Pandemi Covid-19: Apersepsi mahasiswa PIAUD terhadap penerapan multimedia Ezvid - Nurasma; Fenny Anggreni (Aṭfāluna: Journal of Islamic Early Childhood Education, 2020)
The purpose of this study was to determine students' perceptions of the application of Ezvid multimedia in the PIAUD IAIN Langsa Study Program. This research was conducted due to the outbreak of the COVID-19 pandemic where lectures were conducted online in April 2020. So that lecturers need multimedia in teaching to help deliver material to students, one of which is using Ezvid Multimedia. The method in this study uses a descriptive quantitative research approach. Data collection techniques used questionnaires and percentage of data analysis. With a sample of 59 students from the PIAUD study program following the Worship Practices course. The results of this study indicate that most students agree with the implementation of e-learning multimedia based on Ezvid in the Department of Islamic Early Childhood Education, IAIN Langsa. This was evidenced by the percentage value of 61.4% obtained from the questionnaire results, then almost half of them disagree with a percentage of 27.7 %, and a small proportion strongly disagreed with the percentage of 2.9%. If it is seen from the percentage value that most of the students agree with the application of e-learning multimedia based on Ezvid in the PIAUD IAIN Langsa Study Program. So that the response of students to the application of e-learning multimedia based on Ezvid in IAIN Langsa PIAUD Study Program most of the students agree. So that Ezvid multimedia can be applied by lecturers in delivering lectures both online and offline.